ANALISIS FAKTOR KUALITAS LAYANAN DAN NILAI PELANGGAN TERHADAP LOYALITAS PELANGGAN BJB SYARIAH KCP BOGOR JEMBATAN MERAH - Prasetya, Setiawan Bima; Trihantana, Rully; Kusumaningrum, Ria (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
Customer loyalty is a very important factor in increasing revenue and reducing company business costs. This is because customer loyalty is a form of customer loyalty to the company. This study aims to Knowing the service quality factors partially influence customer loyalty. Knowing the customer value factor has a partial effect on customer loyalty. Knowing the factors of service quality and customer value simultaneously influence customer loyalty. This type of research is quantitative with data collection methods using primary data obtained through questionnaires. Sampling amounted to 96 respondents. The method used to test the hypothesis is multiple linear regression, t test, f test, and the coefficient of determination (R square). The results of this study indicate service quality (X1) t count 4.266 > t table 1.969 with a resulting sig value of 0.000 <0.05 and customer value (X2) t count 7.416 > t table 1.969 with a resulting sig value of 0.000 <0.05 So it can be concluded that the variables of service quality and customer value influence customer loyalty. Simultaneously the factors of service quality and customer value have an effect on customer loyalty. This is evidenced by the value (F count 52.266 > F table 3.09) with a sig level of 0.000. While the coefficient of determination R Square is 0.529 or 52.9%, the remaining 47.1% is influenced by other factors.